Studi Kinetika Konsumsi Glukosa oleh Aspergillus Niger dalam Produksi Bioethanol dari Lignoselulosa - Widiyanti, Setyo Erna (INTEK: Jurnal Penelitian, 2017)
Global warming resulted from CO2 level increase in the atmosphere has caused elevation of earth temperature and uncertain climate changes. To prevent the rise of CO2 in the atmosphere can be done by using biomass fuel such as bioethanol. The raw materials of bioethanol can be derived from oil palm empty fruit bunch. Enzymatic hydrolysis utilizes cellulase-producing fungus and in this research, Aspergillus niger was chosen. The glucose produced is consumed by A niger as carbon source and this is undesirable, therefore it should be minimized as low as possible. Knowing the rate of glucose consumption is important to have a model of the hydrolysis reaction rate which will be helpful in the design process on an industrial scale hydrolysis reactor. This study aimed to determine the equations that can be used to approximate the growth rate of A. niger, glucose consumption, the formation of citric acid, and the kinetic parameters used to modeling the kinetics of glucose consumption by A. niger. Kinetics of glucose consumption by A. niger was studied in batch system with variation of initial glucose concentration of 30, 50, 70 g/l. The growth rate of A. niger, glucose consumption, and the formation of citric acid were modeled using 3 equations; i.e. Monod with non-competitive product inhibition, Luedeking-Piret, and Luedeking-Piret growth associated product formation, respectively. The values of kinetic parameters such as μmax, Ks, Kp, were 0.65 hour-1, 157.5 g/l, 0.3 g/l, for initial glucose concentration of 30, 50, 70 g/l, respectively. The values of α (kinetic parameter for growth associated product formation and α would be equal to Yp/x) and Yx/s were 0.4903, 0.8531, 0.9863; 0.5124, 0.2704, 0.2381, for initial glucose concentration of 30, 50, 70 g/l, respectively. Higher initial glucose concentration would increase α but it lowered Yx/s.